Characterization of cross-country cycling coaches (Research, Society and Development, 2021)
The study aimed to evaluate the profile of cross-country cycling coaches. The sample consisted of 20 cycling coaches aged between 26 and 50 years old and who worked on the training prescription for cyclists. All volunteers answered a semi-structured questionnaire that addressed topics such as: coaches' biography; working time as a coach, how to keep up to date, types and forms of periodization, use of software to monitor athletes and the psychological aspects of the training process. Data were analyzed quantitatively through the distribution of absolute and relative frequency. It is observed that 55% of the coaches had already worked for more than 15 years in cycling and 35% of the sample had also worked for more than 15 years with high-performance athletes. It was also possible to verify that 100% of the sample is kept up-to-date in relation to their knowledge related to the sport, with 85% of these coaches seeking this knowledge through courses, congresses or scientific seminars. The main results showed that most coaches had at least 15 years of experience in the profession, in addition, all coaches analyzed stated that they keep up-to-date in relation to the literature on the studied modality.